Determinants and Consequences of Population Trends in Sub-Saharan Africa - IVANOV Sergey Felixovich (Ученые записки Института Африки Российской академии наук)
During the universal demographic transition, the traditional type of population reproduction, characterized by high mortality and high fertility, is transformed into a type of reproduction in which both components are at a low level. The demographic transition is not taking place in a social vacuum, but under the influence of many social factors, including the growth of education and economic development. Reducing child mortality is a sine qua non for changing reproductive behavior. Declines in mortality and fertility are usually separated by long periods when population growth is accelerating. The population explosion is fading away in most countries of Asia and Latin America because they have passed the main part of the demographic transition. In Africa, the decline in child mortality began later and is still in the incipient phase. As a result, fertility, although declining in recent decades in most countries, is declining slowly and remains high. The region as a whole is in the early stage of the demographic transition: the population is growing rapidly and it is not expected to stabilize until the end of the century. Most of the economic and social consequences of rapid population growth are negative. Their conceptualization takes place within the framework of the neo-Malthusian paradigm, which made it possible to substantiate demographic policy based on family planning programs that have proven their effectiveness in different regions of the world. The negative, and sometimes disastrous, consequences of rapid population growth are particularly pronounced in Africa. Anti-Malthusianism is less inclined towards scientific argumentation, and its main goal is not pragmatic solutions to problems, but ideological proclamations, although some anti-Malthusian concepts have positive potential. The concept of the demographic dividend, developed in recent decades, makes it possible to remove the contradictions between two opposing paradigms, since it shifts the emphasis from the negative consequences of rapid population growth to the positive consequences of changes in the population age structure during the demographic transition. The demographic transition in Africa needs to be accelerated, and policies are able to do this without relying on the impractical assumptions of fast economic growth. Three interrelated factors are critical: development of education, radical reduction in child mortality and strengthening of family planning programs.